Is apology the best strategy to mitigate online firestorms in social media? - Souto, D.; Neves, H.; Loureiro, S. M. C. (2020 Global Marketing Conference at Seoul Proceedings, 2020)
Purpose – To provide a comparative overview with respect to the employment of two different crisis communication strategies, namely corrective action vs. apology, in the wake of an online firestorm and to avoid its further escalation. Design/methodology/approach – A 2x3 factorial experimental design was implemented, comprising two levels of image repair strategies (corrective action; apology), and three levels of online firestorm triggers (unethical behaviour; core business problem; communication issue). A total of 564 valid responses were collected by means of an online questionnaire. Findings - Corrective action, as image repair strategy, is more effective than an apology following core business and communication related incidents, whilst neither of the strategies differ in their effects following unethical behaviour incidents. Furthermore, the effect of image repair strategy on perceptions, attitudes and behavioural intentions is moderated and mediated by users’ attribution related to companies´ responsibility and brand attitude, respectively. Last, the absence of an organizational response following an incident has a negative effect on users’ brand attitude in an online setting. Practical implications – Contribution towards the body of knowledge of crisis communication and crisis management fields in online settings. Originality/value – This is the first paper that integrates a comparative overview of CCS’ effectiveness into the management of online firestorms.